The Relationship between Hypertension History, Smoking Degree, and Ultraviolet (UV) Exposure to The Incidence of Seniilis Cataracts at Praya Regional General Hospital - Khaidir Imam Paqih; Sri Subekti; Sahrun; Dian Rahadianti (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Senile cataract is the leading cause of blindness and remains a significant public health problem, particularly among the elderly population. This condition is multifactorial and influenced by various risk factors, including a history of hypertension, smoking intensity, and exposure to ultraviolet (UV) radiation. This study aimed to analyze the association between a history of hypertension, smoking intensity, and ultraviolet (UV) radiation exposure with the occurrence of senile cataract at Praya Regional General Hospital. Methods: This study employed an analytical observational design with a cross-sectional approach. The study subjects consisted of patients with senile cataract and non-cataract patients who met the inclusion and exclusion criteria. Data were collected through interviews, questionnaires, and medical records. Statistical analysis was performed using the chi-square test and Fisher's exact test with a significance level of 0.05. Results: The characteristics of the respondents were predominantly female, with 44 individuals (53.7%), and the largest age group was 60–69 years, comprising 39 individuals (47.6%). In terms of occupation, most respondents were farmers, totaling 37 individuals (45.1%), followed by housewives with 30 individuals (36.6%). The analysis showed that a history of hypertension was significantly associated with the occurrence of senile cataract (p = 0.007). Meanwhile, smoking intensity (p = 0.316) and ultraviolet (UV) radiation exposure (p = 1.000) were not significantly associated with the occurrence of senile cataract. Conclusion: A history of hypertension is a risk factor associated with senile cataract, whereas smoking intensity and ultraviolet radiation exposure were not proven to have a significant association. Continuous screening and health education efforts are needed to control modifiable risk factors in order to reduce the incidence of senile cataract.